Solitary Fibrous Tumor of the Peritoneal Cavity and Greater Omentum: Case Report and Review of the Literature - Gendvilaitė, Neda; Šeinin, Dmitrij; Beržanskas, Laurynas; Poškus, Tomas (Acta medica Lituanica, 2023)
Background: The solitary fibrous tumor is a rare soft tissue mesenchymal tumor which typically arises from the pleura but may be found anywhere in the body. Abdominal localizations are very rare. The solitary fibrous tumor is classified into two forms, pleural and extrapleural, and morphologically they resemble each other. The diagnostics of the tumor is usually accidental because usually there are no clinical symptoms. The main treatment of the solitary fibrous tumor is the surgical removal of the tumor while radiotherapy treatment and chemotherapy outcomes remain unclear due to the rarity of the tumor and lack of data. Case presentation: We report the case of the 32-year-old man who was diagnosed with the solitary fibrous tumor of the peritoneal cavity. Laparotomy was performed. A grayish-white, stiff, coarse-grained tumor about 11 cm in diameter of the greater omentum was found and radical omentectomy with tumor removal were performed. Postoperative course was uneventful and the patient is well with no signs of recurrence on the CT scan of the chest and abdomen and MRI of the pelvis at 6 months after surgery. Conclusions: The solitary fibrous tumor is a rare condition. It is a borderline-malignant tumor but may cause serious complications if not treated. Due to the absence of clinical symptoms, the tumor is usually detected accidentally. The radical surgical removal of the tumor is the most optimal treatment.